A critical review of the Nigerian energy scenario (2013)
Abundant and economical energy is the life blood of modern civilization. Energy poverty continues to be a major constraint to the developmental and economic of Nigeria and the crucial challenge of the energy sector in the country includes the issues of inadequate energy supply, energy security and sustainability. This study appraises critically the current energy scenario in Nigeria and examines the roles of all the primary energy forms in the country as well as alternative energy forms in the provision of adequate energy supply and energy security for the future, particularly as it pertains to the attainment of the country's goals for boosting energy supply as articulated in all its policy and developmental documents. The study identified poor energy mix, slow implementation of policy and inadequate private sector participation as major constraints and challenges of the energy sector and recommends appropriate strategies to improve the energy scenario in the country.